Attitudes and behaviours regarding of adults towards fat products containing fat available in food trading - Platta, A.; Radzymińska, M. (Scientific Journal of Gdynia Maritime University, 2017)
The main aim of the research was an evaluation of dietary attitudes and behaviours regarding adults living in the small city in the Pomeranian province food products for them earlier with a low and high content of fats in overall. The research had been conducted among the group of 160 persons. A scale of the dietary neophobia was the foundation of assessment of attitudes according to the examined group of respondents – Food Neophobia Scale (FNS) by Pliner i Hobden (1992) and Food Attitude Survey (FAS-R) by Frank i van der Klaauw (1994), by means of which the tendency of respondents to approval of products was assessed and which earlier never ate. It has been shown that the examined group of adults had been characterized by the highest level of the dietary neophobia and didn’t demonstrate will of trying food products unknown for them earlier with a low and high content of fats in overall.